Evaluasi Efektivitas Manajemen Pembiayaan Pendidikan Menggunakan Model CIPP di Sekolah Menengah Atas Swasta - Riyanti, Triska; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
Education is one of the main pillars in sustainable national development. Effective financial management in schools is crucial to ensuring the quality of education, especially in private schools that often face challenges in managing resources. This study aims to evaluate the effectiveness of educational financial management at SMA PGRI Rancaekek using the Context, Input, Process, Product (CIPP) model. The research methodology is descriptive quantitative, with data collected through observations, questionnaires, and interviews with 50 purposively selected respondents. The findings reveal that the "Process" category achieved the highest score (82.10%), while the "Context" category had the lowest score (74.43%). These results indicate that although the financial management implementation is functioning well, external support and policy frameworks still need improvement. This research contributes to the educational management literature by offering new insights into the application of the CIPP model in private schools. The implications of this study include recommendations for enhancing policies and financial management practices in other private schools, which could ultimately strengthen the overall quality of education.